Utilizing Transformation Technology to Optimize Operational Management - Musdalifah, St. (Manunggal Halim Jaya, 2025)
Transformation technology is key to supporting the optimization of company operational management. With automation, data analysis, and system integration, companies can improve work efficiency, reduce errors, and accelerate decision-making. However, the implementation of this technology faces various challenges, such as high costs, resistance to change, and infrastructure limitations. This study uses a literature study method to examine the benefits and challenges of transformation technology in operational management. The results of the study show that with good planning and adequate training, companies can overcome obstacles and maximize the potential of this technology. Therefore, transformation technology is an important need to improve company competitiveness in the digital era.